A German experience: The challenges of mediating 'ideal-type' transition management in Ludwigsburg. - Hölscher, Katharina; Wittmayer, Julia M. (Springer, 2018)
When the city of Ludwigsburg in Germany experimented with the transition management approach, it had already formulated ambitious sustainability strategies and programmes, institutionalised sustainability in a cross-sectional city department and established a variety of participatory processes to collect citizen input for strategic planning. In this chapter, we reflect on the transition management process in Ludwigsburg and its results against the backdrop of how 'ideal-type' transition management got mediated in a context with well-developed sustainability strategies and participatory planning processes. The case of transition management in Ludwigsburg reveals several issues that relate to a questioning of the distinctiveness of transition management as co-creation process, its 'added value' and its fit with existing policies and planning processes. The process outcomes might be an indication of challenges in that regard: the results were treated as 'input' to the city government's plans, were not able to inspire 'transformative' thinking, did not result in concrete actions and, finally, roles and relationships of the city government vis-à-vis the citizens were largely re-confirmed. Nevertheless, the results do include new ideas about the future of Ludwigsburg, build on a systemic perspective and the experience with the new methodology triggered the involved policy officers to reflect on the city government's current inflexible and narrow approaches to participation in city planning.
Keywords: Nachhaltige Stadtentwicklung; Akteur; Transformation; Management